Static Analysis-based program evolution support in the common lisp framework - Narayanswamy, K. (Proceedings of the 10th international conference on Software engineering, 1988)
The Common Lisp Framework(CLF) is an object-oriented environment to support the development and maintenance of programs written in the language Common Lisp. A static analysis tool, which is part of CLF, supports program evolution in CLF. Since the effectiveness of our approach stems from the basic design and architecture of CLF, we provide an overview of the relevant features of CLF. The static analysis tool asserts the static properties of program objects definitions into the CLF objectbase. CLF's general mechanism to add rules to the objectbase provides the conceptual basis to respond to changes in the static properties of program objects in several interesting ways - from programming routine responses to program changes to viewing program alterations idiomatically.